The impact of structured physical activity on glycaemic control in diabetes prevention programmes: A systematic review - Joseph Edwards; Hassan Hosseinzadeh (Proceedings of Singapore Healthcare, 2018)
Background: Seven landmark randomised controlled trials, with some that began as early as the 1990s, observed the prediabetic state, namely, impaired glucose tolerance and impaired fasting glucose conditions, against the impact of lifestyle interventions such as physical activity, to prevent or delay the onset of type 2 diabetes mellitus. In addition to the landmark trials, this systematic review examines 14 studies that retained a focus on prediabetic individuals and measured the efficacy of physical activity on improving glucose tolerance. Results: Type, duration and intensity of structured physical activity can have unique benefits to prediabetic individuals. It is posited that diabetes prevention programmes must target prediabetic individuals as belonging to a high-risk group, separate and distinct from those identified with overall risk factors. While the transition from prediabetes to type 2 diabetes mellitus is not completely deterministic, the conversion rate is phenomenally higher among those with impaired glucose tolerance than those with normal glucose levels. Conclusion: Tenets of health behaviour models do support inferences that prediabetic individuals are potentially more inclined to weighing the risks and benefits of progressive illnesses and would therefore be more receptive to active participation in interventions. More research is required to develop evidence-based diabetes prevention programmes linked to structured physical activity intervention.